Upregulation of prostaglandin E by inducible microsomal prostaglandin E synthase-1 in colon cancer - Young Hun Kim; Kyung Jong Kim (Annals of Coloproctology, 2022)
Purpose Prostaglandin E2 (PGE2) is known to promote carcinogenesis and cancer progression in colon cancer. Enzymes involved in the metabolism of PGE2 include cyclooxygenase (COX)-2, microsomal prostaglandin E synthase-1 (mPGES-1), and 15-prostaglandin dehydrogenase (15-PGDH). The current study aims to determine how PGE2 is expressed by examining patients with colorectal cancer and evaluating colon cancer cells to gain insight into changes in relevant enzymes upon induction of PGE2. Methods The concentration of PGE2 was measured in tumor tissues and adjacent normal mucosal tissues of 26 patients with colon cancer. The expression of COX-1, COX-2, mPGES-1, and 15-PGDH proteins was measured. The concentration of PGE2 in FET colon cancer cells was measured both in the initial status and after stimulation by tumor necrosis factor (TNF)-α. The expression levels of PGE2-related enzymes were measured as well. Results There was no significant difference in the average concentration of PGE2, which was measured at 453.1 pg/mL in cancer tissues and 401.2 pg/mL in normal mucosa. Among PGE2-related enzymes, 15-PGDH was expressed at a lower level in tumor cells than in normal mucosa. In colon cancer cells, PGE2 was found to be upregulated upon stimulation by TNF-α, which led to strong induction of mPGES-1 without any change in the expression of COX-2 among the PGE2-related enzymes. Conclusion These results demonstrated that PGE2 can be induced by stimuli such as TNF-α, and suggest that activation of mPGES-1 is more closely related than that of COX-2 in the induction of PGE2 on colon cancer.